2015
DOI: 10.1177/1948550614567358
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Others’ Feelings

Abstract: Recent research has explored the relationship between social hierarchy and empathic accuracy—the ability to accurately infer other people’s mental states. In the current research, we tested the hypothesis that, regardless of one’s personal level of status and power, simply believing that social inequality is natural and morally acceptable (e.g., endorsing social dominance orientation, or SDO) would be negatively associated with empathic accuracy. In a sample of managers, a group for whom empathic accuracy is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(5 citation statements)
references
References 108 publications
(148 reference statements)
0
4
0
1
Order By: Relevance
“…We did, however, measure level of education, which correlates positively with SES [57,58], and we found that covarying education level did not alter our pattern of findings. Furthermore, SES is negatively, not positively associated with at least one of the socio-cognitive variables we measured, namely our measure of mind accuracy, the RMET [59,60].…”
Section: The Art As a Proxy For Fiction Readingmentioning
confidence: 86%
“…We did, however, measure level of education, which correlates positively with SES [57,58], and we found that covarying education level did not alter our pattern of findings. Furthermore, SES is negatively, not positively associated with at least one of the socio-cognitive variables we measured, namely our measure of mind accuracy, the RMET [59,60].…”
Section: The Art As a Proxy For Fiction Readingmentioning
confidence: 86%
“…Nonetheless, Kline (2016, p. 264) emphasizes the importance of evaluating model fit against multiple fit indices, “Because a single statistic reflects only a particular aspect of fit, a favorable value of that statistic does not by itself indicate acceptable fit.” This supports the rejection of the single factor model due to the inconsistent results across key model fit measures. Two other studies (Benau et al, 2020; Sherman et al, 2015) briefly report the results of a CFA for a single-factor model as evidence for acceptable internal consistency of the RMET. While the authors of both studies stated that they found good model fit, the fit statistics that they provided were not comprehensive and did not include the fit statistics that showed poor model fit in the analyses conducted by Olderbak et al (2015) and Black (2019).…”
Section: The Rmetmentioning
confidence: 99%
“…Otros trabajos que abordan otras perspectivas como la Orientación de la Dominancia Social (ODS), la cual se refiere a que los individuos que tienen alta dominancia social son aquellos que aceptan la inequidad social entre los grupos, la jerarquía entre los grupos, como algo natural y que es moralmente aceptable 30 , han permitido evidenciar que quienes tienen bajos niveles de empatía y altos niveles de ODS tienen menos valores medioambientales (preservación de la naturaleza) 20- 22,54 .…”
Section: Discussionunclassified